Analisis Determinan Pengungkapan Informasi Lingkungan Menggunakan Voluntary Disclosure Theory: Komparasi Pada Industri yang Berbeda - Burhany, Dian Imanina; Afriady, Arif; Mulyandani, Vina Citra (Universitas Pamulang, 2022)
This study aims to determine whether there are differences in the environmental information disclosure in different industries and whether environmental performance and profitability are determinants of environmental information disclosure in different industries, namely environmentally sensitive industries and environmentally insensitive industries. This research is comparative and quantitative research. The research sample is companies listed on the Indonesia Stock Exchange that publish sustainability report and annual report year 2021 and participate in PROPER period 2020d. The research model is analyzed and tested using difference test and Partial Least Square with the Structural Equation Model (PLS-SEM). Research data is secondary data sourced from company sustainability reports and annual reports as well as PROPER publication by the Ministry of Environment and Forestry. Study results found that there is no difference in environmental information disclosure in different industries, environmental performance is a determinant that has a positive effect on environmental information disclosure in environmentally sensitive industries, environmental performance is not a determinant of environmental information disclosure in environmentally insensitive industries, profitability is a determinant that has a negative effect on environmental information disclosure in environmentally sensitive industries, and profitability is a determinant that has a negative effect on environmental information disclosure in environmentally insensitive industries.